Polarization Measurement of Cs Using the Pump Laser Beam - Rujie Li; Wei Quan; Jiancheng Fang (IEEE Photonics Journal, 2017)
In the optically pumped systems, the spin polarization of the atoms is generally derived by employing additional modulations, in which way an extra perturbation will be introduced and thus affect the normal operation of the sensors. By investigating the absorption principle of the circularly polarized pump laser, here, we demonstrate the feasibility of extracting the electron-spin polarization from the transmitted intensity of the pump beam. This scheme can detect real-time polarization without disturbing the normal operation of the sensor, and the experimental result agrees well with the theory. This research is of value to the research and development of optically pumped systems, especially the magnetometer, and the comagnetometer operated in the spin-exchange relaxation free regime.